Communist Political Systems - White, Stephen. author. aut Link
VIII, 293 p.
Keywords: The third edition of this text provides a background to the politics of China, Eastern Europe and what was the Soviet Union. The book has been rewritten throughout to reflect the emergence of pluralist multi-party systems and non Communist governments are marked.